Education, Equity and Inclusion Teaching and Learning for a Sustainable North - Hirshberg, Diane B.; Beaton, Mhairi C.; Maxwell, Gregor; Turunen, Tuija; Peltokorpi, Janette (Springer Polar Sciences, 2023)
This open access book provides a current view on education, equity and inclusion within the lens of education for a sustainable North. The first book published by the University of the Arctic Thematic Network for Teacher Education for Social Justice and Diversity (Including the North: A comparative study of the policies on inclusion and equity in the circumpolar North, 2019) highlighted policies of inclusion and equity in education in national and regional contexts. This new book explores in more depth the provision of education across the north, focusing on challenges and innovations in meeting the needs of diverse learners in remote and rapidly changing contexts. While many texts address issues of equity, inclusion and diversity, they are almost all focused on the global South, and miss the lessons that can be learned from Northern regions. This book offers an extended essay on teaching and learning through various perspectives and experiences with the aim of creating a more sustainable North. It is structured around two main themes: 1) Supporting Teachers for Diversity and Inclusion in the Classroom including consideration of language and identity issues, 2) Engendering community solutions to structural and geographical challenges in education in the circumpolar north.